Pelatihan Teknik Pembuatan Pakan Sapi Bali di Kelompok Peternak Patut Patuh Patju Kelurahan Ampenan Selatan Kecamatan Ampenan Kota Mataram - Muhamad Amin; Sofyan D Hasan; Syamsul Hidayat Dilaga; Oscar Yanuarianto; Dahlanuddin Dahlanuddin (Jurnal Gema Ngabdi, 2022)
As an effort to improve the knowledge and skills of farmers in rural areas, service activities have been carried out with the topic "Training on Bali Cattle Feed Making Techniques in the Patut Patuh Patju Farmer Group, South Ampenan Village, Ampenan Sub-district, Mataram City". This service activity was held on the grounds that farmers in Ampenan Selatan Village often have difficulty meeting the needs of their livestock for forage, especially during the dry season, so this sometimes has an unwanted negative impact such as the occurrence of cases of death and disease in livestock as a result of declining livestock conditions. This is due to the ignorance of the farmers in an effort to overcome the shortage of forage during the dry season. This community service activity will be carried out with three methods, namely the lecture, written and demonstration methods. With the lecture method delivered on the understanding and explanation of silage and Ammoniation Fermentation (Amofer). Through the written method, it was delivered by giving a brochure containing how to make silage and make Amofer rice straw. Meanwhile, with the demonstration method, the farmers immediately practiced the preservation and processing method with Silage and Amofer technology. Based on the results of monitoring during the activity, the results of the questions and answers and the enthusiasm of the participants, it was seen that the farmers had just realized the importance of the role of nutrition for livestock, were willing to apply feed preservation and processing technology, and it could also be seen that they had no difficulty in adopting the material provided. So overall this activity can be said to be quite successful. Recognizing the limitations of breeders in terms of conservation and feed processing which is an alternative for providing feed in the dry season, the service team suggests that this kind of activity should be continued so that the expected livestock production can be achieved.